Management of Dystocia Due to Oversize Foetus through Fetotomy in a Crossbred Heifer - Patel, A.J.; Prajapati, A.R.; Patel, J.A.; Parmar, J.J.; Parmar , S.C. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Dystocia is defined as delayed or difficult calving, something requiring significant human assistance (Lombard et al., 2007). The most common cause of dystocia in cattle is fetopelvic disproportion. This is most common in heifers when size of the fetus is normal but the maternal pelvis is not big enough, or the fetus is unusually large and cannot be delivered through a pelvic canal of normal size. Dystocia is significantly higher in first and second parity cows and buffalo, and that dystocia of fetal origin is common in cows (65.62%) but less frequent (40.17%) in buffalo (Purohit et al., 2012). The present paper reports successful management of dystocia due to foetal oversize through fetotomy in a crossbred heifer.